Pengaruh Kompetensi Terhadap Kinerja Karyawan Melalui Kepuasan Kerja : Studi Literatur - Achmad Farid Nur Rijal (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2020)
Article investigate the influence of competence on performance, competence on job satisfaction, job satisfaction on performace, and competence on performance through job satisfaction. The literature study were based on empirical studies from any national and international journals. Data collected by using a search engine methods. The results suggest that competence has positive significant effect on performance, competence has positive significant effect on job satisfaction,job satisfaction has positive significant effect on performace, and competence has positive significant effect on job satisfaction through job satisfaction.